Religious Practices and Local Magic of Inland Malay Society in West Kalimantan - Hermansyah Hermansyah (Graduate Program of Pontianak Institute of Islamic Studies, 2016)
Belief and practice as part of culture which exists in society is the result of a dynamic process that is growing and developing, and affected by both internal and external aspects of the society. All of this is a manifestation of a continuity of the treasures of humanity. Derivation and transfer of a culture toward forming a new more complex culture is natural and inevitable. There is no culture and civilization in the world built without relationship and interchange with other cultures and civilizations. It is also the case with the religious life of the rural community in West Kalimantan which is the subject of the study in this article. This continuity shows that local communities have a vibrant culture passed down from one generation to the next. The existence of tradition heritage recorded in magic called ilmu in inland Islamic societies of West Kalimantan shows that their peaceful process of accepting Islam since its spread, to a certain extent, accommodates local culture. The dialectic process of Islam and local culture serves as an example of religious acceptance in a massive fashion in a region far away from the coastal area.